Understanding Mathematical Concepts in Terms of Learning Style and Intellectual Intelligence - Ridwan Awalian Firdaus (Universitas Sebelas Maret, 2025)
The purpose of this study to determine the effect of learning styles on students' understanding of mathematical concepts, the influence of intellectual intelligence on students' understanding of mathematical concepts and the effect of the interaction of learning styles and intellectual intelligence on students' understanding of mathematical concepts. The research method used is ex post facto. The sample size 123 students consist of 32 students with visual type, 54 students with auditory type and 37 students with kinesthetic type, the sampling technique used is cluster sampling. Data collection was carried out by giving a test of understanding mathematical concepts and distributing student learning style questionnaires. The results showed: 1). There is an insignificant effect of learning style on the understanding of mathematical concepts in grade 10 high school students in Bogor City. This is evidenced by the value of sig. = 0.573 > 0.05 and FH = 0.559 So there is no difference in understanding of mathematical concepts between groups of students with visual, auditory and kinesthetic learning styles. This means that students with visual, auditory, and kinesthetic learning styles have the same abilities. 2). There is a significant influence of intellectual intelligence on the understanding of mathematical concepts in grade 10 high school students in the city of Bogor. This is evidenced by the value of sig. = 0.00 < 0.05 and FH = 23.34 So there is a difference in understanding of mathematical concepts between groups of students with high intellectual intelligence and low intellectual intelligence. This means that students with high intellectual intelligence have different abilities with low intellectual intelligence. 3). There is an interactive influence that is not significant enough on learning style and intellectual intelligence of the understanding of mathematical concepts in grade 10 high school students in Bogor City. This is evidenced by the value of sig. = 0.821 > 0.05 and FH = 0.197 so no further test is needed.